Constitutive modelling of transient and steady state creep behaviour of type 316LN austenitic stainless steel. (October 2019) - Praveen, C.; Christopher, J.; Ganesan, V.; Reddy, G.V. Prasad; Sasikala, G.; Albert, Shaju K.
Highlights: Sine hyperbolic creep rate law coupled with the evolution of internal stress has been employed to describe the creep deformation behaviour of 316LN SS. Predicted activation volume in the range of 430–870 b 3 indicated the dominance of intersection of forest dislocations and non-conservative motion of jogs during transient creep. Model has been extended towards the prediction of stress-relaxation behaviour of the steel using the parameters derived from the creep data. Abstract: In the present study, sine hyperbolic creep rate law coupled with the evolution of internal stress with time has been employed for modelling transient and steady state creep deformation behaviours of type 316LN austenitic stainless steel (SS). The model predicts the creep strain-time and creep rate-time data appropriately for the stress levels ranging from 120 to 225 MPa at 923 K, with good agreement between experimental and predicted steady state creep rates. At all the stress levels, the predicted internal stress increases with time during transient creep, and it approaches saturation at steady state creep. The predicted increase in internal stress was interrelated to the increase in dislocation density and a decrease in the mean free path during creep deformation. At steady state condition, a decrease in activation volume with an increase in applied stress levels has been observed for the steel. The estimated value of activation volume for the steel demonstrates the dominance of intersection of forest dislocations and non-conservative motion of jogs during transient creep in type 316LN SS. The applicability of the present model has been demonstrated towards the prediction of stress-relaxation behaviour of type 316LN SS based on the power law interrelation between internal stress and applied stress.